2016
DOI: 10.1590/s1980-57642016dn10100003
|View full text |Cite
|
Sign up to set email alerts
|

Phototest for neurocognitive screening in multiple sclerosis

Abstract: Multiple Sclerosis (MS) is one of the most common neurological disorders. Cognitive dysfunction is considered a clinical marker of MS, where approximately half of patients with MS have cognitive impairment.Objective:The Phototest (PT) is a brief cognitive test with high diagnostic sensitivity, accuracy and cost-effectiveness for detecting cognitive deterioration. Our aim was to test the utility of the PT as a neurocognitive screening instrument for MS. Methods:The study enrolled 30 patients with different type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent studies have reported the superiority of the PT in identifying CD in general and MCI in various health contexts 29,50 , including their identification in illiterate or low-schooling subjects 51,52 , showing that PT was one of the most accurate tests to detect suspected CD, especially in patients with lower levels of education or in those coming from different cultural backgrounds. Nevertheless, in a systematic review of BCTs for early detection of dementia in LA elders, Custodio et al 53 reported difficulties in a broad spectrum of BCTs, including MoCA, ACE-R, and the Ineco Frontal screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported the superiority of the PT in identifying CD in general and MCI in various health contexts 29,50 , including their identification in illiterate or low-schooling subjects 51,52 , showing that PT was one of the most accurate tests to detect suspected CD, especially in patients with lower levels of education or in those coming from different cultural backgrounds. Nevertheless, in a systematic review of BCTs for early detection of dementia in LA elders, Custodio et al 53 reported difficulties in a broad spectrum of BCTs, including MoCA, ACE-R, and the Ineco Frontal screening.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Phototest (PT) 23 has demonstrated its usefulness in primary health care centers, since it does not use pencil or paper, which facilitates its performance and evaluation, especially in people with lower educational levels or in those who are illiterate 24,25 . It has a higher sensitivity and specificity than traditional tests with respect to dementia and MCI 26,27 and has shown to be more effective and cheaper than the Mini-Mental State Examination (MMSE) in multiple studies [27][28][29] . Finally, given its structural and managing characteristics, it is believed to be easily adapted to virtual assessment formats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation